2008
DOI: 10.1002/ptr.2687
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum extract attenuates the proliferation of hepatic stellate cells by blocking the PDGF receptor

Abstract: Hepatic fibrosis is an outcome of chronic liver diseases. The activation and proliferation of hepatic stellate cells (HSCs) is a key event in liver injury. The fruiting body of Ganoderma lucidum has long been a popular oriental medicine for treating liver diseases. The aim of this present study was to investigate the antiproliferative effects of the triterpenoid-rich extract (GLT) of G. lucidum in a cell line of rat HSCs (HSC-T6) stimulated with platelet-derived growth factor (PDGF)-BB. DNA synthesis was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Similar to the mechanism above, in the present study, sorafenib is capable of inhibiting cellular proliferation activated by PDGF-BB in a dose-dependent manner in both cell lines. Suppression of proliferation and induction of apoptosis are accompanied by a downregulation of Cyclins and Cdks [19,28]. We also found that sorafenib caused T6 and LX2 cells to undergo arrested growth in the S phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to the mechanism above, in the present study, sorafenib is capable of inhibiting cellular proliferation activated by PDGF-BB in a dose-dependent manner in both cell lines. Suppression of proliferation and induction of apoptosis are accompanied by a downregulation of Cyclins and Cdks [19,28]. We also found that sorafenib caused T6 and LX2 cells to undergo arrested growth in the S phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 95%
“…Rat T6 and human LX2 are well-characterized HSC lines that recapitulate many features of the activated HSC phenotype, including the expression of the PDGFR-b subunit [18,19]. HSCs were cultured in DMEM supplemented with 10% FBS.…”
Section: Cell Lines and Treatment Of Hscsmentioning
confidence: 99%
“…One of the potent biologically active compounds that has been shown to possess diverse and potentially significant pharmacological activities is the bitter triterpenes [2]. Since the first discovery of ganoderic acids A and B, more than 150 types of triterpenes have been isolated from various parts of Ling Zhi [2, 3], among which ganoderic acids A and F (Figure 1) have received considerable attention due to their conspicuous pharmacological properties for example, antihypertensive [4], antinociceptive [5], antioxidative [6], farnesyl protein transferase inhibitory [7], and hepatoprotective activities [8, 9], especially anticancer activity [10–13] which is the most attractive character of this medicinal mushroom. Ganoderic acid A has been reported to suppress growth and invasion of highly invasive human breast cancer cells via downregulation of expression of cyclin-dependent kinase 4 that regulates cell cycle G 1 phase progression, and via suppression of secretion of urokinase-type plasminogen activator that implicates in tumor cell invasion and metastasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several other naturally occurring triterpenoids have demonstrated anti-platelet aggregation activity [21-24] possibly through down-regulation of phosphorylated ERK [23]. In hepatocellular stellate cells, triterpenoid appears to decrease phosphorylation of PDGF-R and AKT [25]. To the best of our knowledge, there are no reports of other synthetic triterpenoids or CDDO derivatives describing an association with increased clotting susceptibility.…”
Section: Discussionmentioning
confidence: 99%